Innovation Strategy of Small Medium Enterprise (SME) Through Public-Private Partnership in Depok City - Anita Maulina; Maya Puspita Dewi (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The rapid growth of SMEs in Depok City is not accompanied by the increase in the capacity of the SMEs itself, especially in terms of innovation. The limited resources that SMEs have, can be supported by the existence of public-private sector partnerships. This research is a qualitative research with data collection techniques through interviews, observation, and literature study. The results show that public-private sector partnerships in Depok City have not been successful in increasing the capacity of SMEs to innovate. This is because the partnership is limited to providing infrastructure and focuses on increasing temporary income. Therefore, the public-private sector partnership should focus on more technical assistance in increasing added value to ensure business continuity for a longer period.